Mucosal Airway Laceration Secondary To Endobronchial Ultrasonography - Amarinder Sandhu; Edmundo Rubio; Susanti Ie; Michael Boyd (Canadian Respiratory Journal)
Endobronchial ultrasound-guided transbronchial needle aspiration is becoming the standard of care for mediastinal sampling to diagnose and stage lung cancer. It is considered to be safe and rivals the gold standard, mediastinoscopy, in safety and accuracy. The present article describes a mucosal airway laceration and pneumothorax associated with the procedure.